Innovation and tradition at the University of Pennsylvania School of Medicine : an anecdotal journey - Cooper, David Y., III, 1924-2013 (University of Pennsylvania Press, 1990)
From the time of its establishment in the eighteenth century until late in the nineteenth century, the University of Pennsylvania's School of Medicine was the most respected medical institution in the United States. Today it is among the leaders in medical education in the U.S. It continues to play a crucial role in the development of medical education, the practice of medicine, and medical research in America. Innovation and Tradition at the University of Pennsylvania School of Medicine: An Anecdotal Journey presents a thoroughly researched, readable history of this important institution. Tracing its growth from a couple of courses at the College of Philadelphia to its 225th anniversary in 1990, the authors highlight the truly remarkable contributions to science and medicine made by members of the school's distinguished faculty including--Benjamin Rush, Caspar Wistar, Joseph Leidy, Simon Flexner, lsador Ravdin, and Britton Chance.